Optimasi pemasaran digital bank syariah - Ummi, Laely Saidatul (Maliki Interdisciplinary Journal, 2024)
In the rapidly developing digital era, marketing optimization is very important for Islamic banks to expand reach and increase customer engagement. This research aims to determine marketing strategies that can optimize the survival of Islamic banks through digital channels. The qualitative research method used was accompanied by in-depth interviews with marketing and management experts from Islamic banks. The results demonstrate a successful marketing strategy that includes sharia-compliant content, personal communication with customers, use of technology in banking, and strategic partnerships with digital financial platforms. By exploiting these factors, Islamic banks can strengthen their brands, attract new customers and retain existing customers. This study provides a valuable guide for Islamic banks to design effective digital marketing strategies that drive sustainable growth in the ever-changing digital era. As a result, Islamic banks can remain relevant and competitive in a banking industry that is increasingly connected digitally.